PENANAMAN SIKAP DISIPLIN SISWA SEBAGAI UPAYA MENUMBUHKAN RASA TANGGUNG JAWAB TERHADAP DIRI SENDIRI DI SD NEGERI 140 PALEMBANG - Ambar Afifah; Sri Maryani; Giska Dwi Febrianti; Samilah Indah; Yusmarika Sri Nustia; Irra Pirta Meliyana; Syasya Askarini; Dhores Mahendra; Mega Prasrihamni (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2026)
Discipline is one of the essential character values that should be instilled from an early age, particularly at the elementary school level, as it plays a significant role in fostering students’ sense of responsibility toward themselves and their surrounding environment. Based on observations conducted during the Field Experience Program (PLP) at SD Negeri 140 Palembang, several students were found to demonstrate low levels of discipline in complying with school regulations, managing their time effectively, and carrying out their duties and responsibilities as learners. This activity aimed to instill disciplinary attitudes as an effort to develop students’ self-responsibility. The methods employed in this program included observation, socialization, habituation, mentoring, and evaluation. The implementation involved providing educational sessions on the importance of discipline, encouraging disciplined behavior during learning activities, and assisting students in applying disciplinary values within the school environment. The results indicated an improvement in students’ understanding of the importance of discipline and a growing awareness of fulfilling their duties and responsibilities independently. In addition, students showed positive behavioral changes, such as arriving at school on time, participating more orderly in classroom activities, maintaining classroom cleanliness, and completing assignments according to established rules. These findings demonstrate that instilling discipline can effectively contribute to the development of responsible character among students from an early age. Therefore, continuous disciplinary habituation through collaboration among schools, teachers, and parents is necessary to support the formation of positive student character. ABSTRAK Disiplin merupakan salah satu nilai karakter yang penting ditanamkan sejak usia sekolah dasar karena berperan dalam membentuk sikap tanggung jawab peserta didik terhadap diri sendiri maupun lingkungan sekitarnya. Namun, berdasarkan hasil observasi selama kegiatan Program Pengenalan Lapangan (PLP) di SD Negeri 140 Palembang, masih ditemukan beberapa siswa yang kurang disiplin dalam mematuhi tata tertib sekolah, mengelola waktu, serta melaksanakan tugas dan kewajiban sebagai peserta didik. Kegiatan ini bertujuan untuk menanamkan sikap disiplin sebagai upaya menumbuhkan rasa tanggung jawab terhadap diri sendiri pada siswa SD Negeri 140 Palembang. Metode yang digunakan dalam kegiatan ini meliputi observasi, sosialisasi, pembiasaan, pendampingan, dan evaluasi. Kegiatan dilaksanakan melalui pemberian edukasi mengenai pentingnya disiplin, pembiasaan perilaku disiplin dalam kegiatan belajar mengajar, serta pendampingan terhadap siswa dalam menerapkan nilai-nilai disiplin di lingkungan sekolah. Hasil kegiatan menunjukkan adanya peningkatan pemahaman siswa mengenai pentingnya disiplin serta tumbuhnya kesadaran untuk melaksanakan tugas dan tanggung jawab secara mandiri. Selain itu, siswa menunjukkan perubahan perilaku yang positif, seperti datang tepat waktu, lebih tertib dalam mengikuti pembelajaran, menjaga kebersihan lingkungan kelas, dan mengerjakan tugas sesuai dengan ketentuan yang diberikan. Melalui kegiatan ini, penanaman sikap disiplin terbukti dapat membantu membentuk karakter tanggung jawab siswa sejak dini. Oleh karena itu, pembiasaan disiplin perlu dilakukan secara berkelanjutan melalui kerja sama antara sekolah, guru, dan orang tua guna mendukung pembentukan karakter peserta didik yang lebih baik.